Analyse du rôle des chercheurs en sciences sociales dans la gestion des déchets radioactifs - Grégoire Lits (VertigO, 2013)
The career of the problem of nuclear waste management (NWM) is characterized by a major shift in the way decisions are made. The formulation of a technical solution does not appear to be sufficient anymore. Regulators need to address both the technical and the “societal aspects” of NWM. Subsequently, one observes the rising of a new consensus, namely that these “societal aspects” can only be properly handled by mobilizing the expertise of the social scientists. Collaboration between nuclear and social scientists is therefore called upon as a way to improve NWM. Based on a critical review of the literature available on the role of social scientists in the governance of nuclear technology, informed by an ethnographic fieldwork conducted in Belgium between 2009 and 2012, this article analyses the different roles that social scientists can actually play and the different ways through which their expertise can be mobilized for managing the “societal aspects” of NWM. Three conclusions can be drawn. First, we point out the existence of a seminal controversy (going back to the late 40’s) opposing sociologists and nuclear engineers regarding their respective responsibilities in the handling of the “societal aspects” of nuclear technologies. Secondly, the analysis of that controversy shows that two different normative framings – two different world views – emerge from the critics developed by the social scientists. These normative framings can be used to understand the frequent discrepancy existing between the expectations of nuclear experts and social scientists regarding their respective roles in decisional processes and management operations. Finally, three ideal-typical modes of engagement for social scientists are constructed that could be used in further research for studying and understanding actual situations of collaboration in NWM.